Obrońca węzła małżeńskiego gwarantem prawdy i sprawiedliwości – refleksje na kanwie przemówienia papieża Franciszka do członków Najwyższego Trybunału Sygnatury Apostolskiej z 8 listopada 2013 r. - Nowicka, Urszula (Ius Matrimoniale, 2014)
Pope Francis, speaking on November 8, 2013 to the members of the Supreme Tribunal of the Apostolic Signatura, returned to the issue reiterated for years – namely to emphasise the role of the defender of the bond in a process. Based on this speech many important issues appear, such as a pastoral good of parties and bound up with it the principle of truth, the role of the defender of the bond in safeguard of this truth and reciprocal relationship between the defender and a judge. It shows that evangelistic activity of the Church is indissolubly connected with the ecclesial administration of justice and that in ecclesiastical courts it is necessary to always have an icon of the Good Shepherd before eyes, which first of all is a righteous Shepherd.